Advances in CAD/CAM/CAE Technologies - Kyratsis, Panagiotis (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
CAD/CAM/CAE technologies find more and more applications in today's industries, e.g., in the automotive, aerospace, and naval sectors. These technologies increase the productivity of engineers and researchers to a great extent, while at the same time allowing their research activities to achieve higher levels of performance. A number of difficult-to-perform design and manufacturing processes can be simulated using more methodologies available, i.e., experimental work combined with statistical tools (regression analysis, analysis of variance, Taguchi methodology, deep learning), finite element analysis applied early enough at the design cycle, CAD-based tools for design optimizations, CAM-based tools for machining optimizations.